(untitled) (Bodhi Path, 2024)
The universe is not governed by the whims of a Creator God or by any other supernatural power or authority. In Buddhism the universe and the life therein are governed by the natural law of Cause and Conditions and conditionally originated phenomena, creating a self –sustaining mechanism. Avijjā (SEED) is the foremost factor in the principle of Dependent Origination. In this paper, we present the principle of Dependent Origination and its pros and cons .The paper is divided into subtitles as the first link of the Dependent Origination, Avijjā- (Ignorance) means Nourishment and Denourishment of Ignorance.